2020
DOI: 10.1002/pmrj.12293
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Testing a Novel 3D Printed Amphibious Lower Limb Prosthesis in a Recreational Pool Setting

Abstract: Introduction Adults with limb amputation and other physical disabilities are less likely to participate in physical activity than adults in the general population and have elevated risk of heart disease and stroke. Swimming is a physical activity often recommended for persons with limb amputation. However, a standard economical swim prosthesis that facilitates easy transition from land to water does not exist. Objective The objectives were (1) to measure ease of first‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…and their mechanical parameters (strength, materials, structure, geometry, weight or complexity) (Alqahtani et al , 2021; Goldstein et al , 2020; Guo Dong et al , 2020; Jarl et al , 2012; Stenvall et al , 2020). According to the evaluation, some participants in a recreational pool scenario found an additively manufactured lower limb prosthesis acceptable and straightforward (Goldstein et al , 2020). With the view to the application of composite materials in the development of prostheses, transtibial lower limb prosthesis had been fabricated using biocomposite materials (polypropylene-reinforced with micro-fibrillated cellulose) and FDM technology.…”
Section: Additive Manufacturing In Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…and their mechanical parameters (strength, materials, structure, geometry, weight or complexity) (Alqahtani et al , 2021; Goldstein et al , 2020; Guo Dong et al , 2020; Jarl et al , 2012; Stenvall et al , 2020). According to the evaluation, some participants in a recreational pool scenario found an additively manufactured lower limb prosthesis acceptable and straightforward (Goldstein et al , 2020). With the view to the application of composite materials in the development of prostheses, transtibial lower limb prosthesis had been fabricated using biocomposite materials (polypropylene-reinforced with micro-fibrillated cellulose) and FDM technology.…”
Section: Additive Manufacturing In Prosthesesmentioning
confidence: 99%
“…Prostheses are evaluated based on their functionality in various activities (walking, running, swimming, etc.) and their mechanical parameters (strength, materials, structure, geometry, weight or complexity) (Alqahtani et al , 2021; Goldstein et al , 2020; Guo Dong et al , 2020; Jarl et al , 2012; Stenvall et al , 2020). According to the evaluation, some participants in a recreational pool scenario found an additively manufactured lower limb prosthesis acceptable and straightforward (Goldstein et al , 2020).…”
Section: Additive Manufacturing In Prosthesesmentioning
confidence: 99%
“…A recent scoping review [ 18 ] only found 11 articles that covered the implications of 3D printing in the field of lower limb amputation, but they concluded that it was a promising advancement in modern prosthetic fabrication. Among the existing studies, the focus has mainly been on user experiences and improved functionality of the AM-fabricated prosthetic parts using commercial materials [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%